PEMBANGUNAN KAMPUNG BAHARI DALAM PERSPEKTIF SUSTAINABLE DEVELOPMENT DI KAWASAN PESISIR TAMBAKLOROK KOTA SEMARANG - Naila Authori; Kismartini Kismartini; R Slamet Santoso (Journal of Public Policy and Management Review, 2022)
The policy for the development of Kampung Bahari Tambaklorok is a special instruction from the President of the Republic of Indonesia, Joko Widodo in 2014 to the Semarang City Government. The Kampung Bahari program is described in detail in the Land and Building Planning Plan (RTBL) of Kampung Bahari Tambaklorok for 2016 which was prepared based on the Semarang City Regional Spatial Plan (RTRW) for 2011 – 2030 and the Regional Medium Term Development Plan (RPJMD) for the City of Semarang 2016 – 2021. Through a descriptive qualitative approach, this study aims to analyze the implementation and constraints of the Kampung Bahari Tambaklorok program in a sustainable development perspective. The results of the study indicate that the development policy of the Kampung Bahari Tambaklorok program aims to realize the principle of sustainable coastal area development based on an advanced, beautiful, and prosperous local economic environment. In its implementation, Kampung Bahari Tambaklorok sustainable development policy has not been fully fulfilled. Constraints faced in the implementation of development policies are the absence of a contribution to the Regional Original Income (PAD) of Semarang City, there is still resistance from community groups, social empowerment programs have not been implemented, changes to existing areas, the absence of legal and independent regulations regarding the village program, permits the lease-to-use asset has not been approved by PT. Pelindo, as well as institutional complexity. This study provides recommendations that Regional Original Revenue (PAD) can be obtained from development programs that have been completed, there is a need for synergy and synchronization between stakeholders from each development plan, the need for a review and evaluation of the implementation of development programs, the need for transparency in program implementation, and protection of the area through construction sheet pile needs to be implemented immediately, it will be an obstacle to other development programs